Russian thistle (Salsola tragus L.) serotiny promotes simultaneous aerial and soil seedbanks - Geddes, Charles M.; Pittman, Mattea M. (Frontiers in Agronomy, 2024)
Some plant species retain mature seeds in plant canopies aboveground which are released later during opportune windows for germination and establishment. This process, known as serotiny, can lead to aerial seedbanks that exist simultaneously with soil seedbanks. However, little is known about how serotiny affects the persistence of weed seeds in the aerial seedbank. A randomized-stratified survey of 117 sites in southern Alberta, Canada, was conducted in 2022 to determine whether the summer-annual tumbleweed Russian thistle (Salsola tragus L.) exhibits seed serotiny. The observational study confirmed that Russian thistle plants exhibit serotiny and that the seeds can exist simultaneously in aerial and soil seedbanks. On average, the plants sampled retained 332 ± 62 viable seeds plant-1 seven to eight months after senescence. This time frame followed winter and emergence of the subsequent generation of plants from the soil seedbank. Russian thistle plants that were attached to the soil retained about double (P = 0.0274) the number of seeds (549 ± 133 viable seeds plant-1) than those detached from the soil (270 ± 71 viable seeds plant-1), likely due to seeds dislodging during movement of the tumbleweeds with prevailing winds. Seeds persisting in aerial seedbanks could evade decay, predation, or lethal germination leading to seed mortality in the soil seedbank, and increase the likelihood of seed persistence and successful establishment of new plants in stressful environments.